Association between cardiometabolic index and abdominal aortic calcification in US adults from the NHANES - Minjiang Ren; Yifan Shen; Ye Yuan; Zhiyu Han; Yun Zhong; Shiming Liu (Scientific Reports)
Abstract Abdominal aortic calcification (AAC) and atherosclerosis are prevalent conditions among older adults, and recent research suggests that their association may extend beyond the effects of aging alone. An essential instrument for determining the possibility of cardiovascular disease (CVD) is the cardiometabolic index (CMI), a new lipid-based index sensitive to visceral obesity. However, little has been established about the relationship between CMI and AAC. We examined CMI and AAC data from the National Health and Nutrition Examination Survey (NHANES) conducted in 2013–2014 for this study. The relationship between AAC, severe abdominal aortic calcification (SAAC), and CMI was assessed using multiple linear and logistic regression models. The overall trend was visualized using smoothed curve modeling. Subgroup analyses were conducted to find possible moderating factors. Among the 2704 participants included, those with higher CMI levels exhibited much greater AAC scores and a higher prevalence of SAAC. In model 3, elevated CMI positively correlated with AAC (0.25 (0.09, 0.41)) and with the odds of SAAC (OR = 1.35 (1.09, 1.67)). Participants in the highest CMI quartile had an AAC score that was 0.65 units higher (β = 0.65 (0.26, 1.04)) and an 114% higher risk of SAAC (OR = 2.14 (1.29, 3.54)). Subgroup analyses indicated sex and smoking status significantly modified the relationship between CMI, AAC, and SAAC, while previously diagnosed with congestive heart failure (CHF) and heart attack significantly moderated the association between CMI and AAC. These results imply that greater AAC scores and a higher risk of SAAC are linked to heightened CMI, which represents visceral fat storage and disturbed lipid metabolism. Our findings indicate that CMI is correlated with AAC in certain demographic and cardiovascular subgroups, suggesting its potential as an exploratory indicator of elevated AAC risk in these populations.